Hairesis, Diatribe, Ekklesia: griechische Schulgeschichte und das Lukanische Geschichtswerk - Cancik, Hubert (Early christianity, 2011)
In this essay, the »schools« of the ancient philosophers as described by Lucian of Samosata and Numenius of Apameia – both 2nd century CE – are compared with the formation of the »ekklesia« in Luke-Acts. For example, Numenius narrates the history of the decadence of the Platonic Academy, marked by stasis/σιασς and schisma. He insists on reformation through a return to the origin of the school, that is, to Pythagoras. Luke narrates the genesis and growth of a charismatic religious group and its transformation into a universal institution, given the name of a political assembly (εκκλσíα). The essay's comparisons exhibit both similarities and differences (e.g., concerning growth, schism, diadoche, teacher) between the different groups.